Membangun Karakter Islami Melalui Al Islam dan Kemuhammadiyahan [Studi Analisis Perpres Nomer 87 Tahun 2017 tentang Penguatan Pendidikan Karakter (PPK)] - Huda, Hairul (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2019)
Human activity and behavior are largely influenced by the surrounding environment affecting every character he/she has been endowed innately from birth. Of special concerns for us is how deviations associated with, or caused by, human behaviour such as burglary, murder, and even corruption committed when they are appointed to be a leader in this country. Considering that Islamic values are highly concerned with educating behaviour, moral, and character as exemplified by Prophet Muhammad PBUH. Charity actions in the field of education performed by Muhammadiyah have, to some extent, strengthened religious values, honesty, and intellectuality by means of providing a course unit named Al-Islam and Kemuhammadiyahan (AIK). The present study employed a library research methodology. There are two primary sources examined in this study. AIK moduls issued by Muhammadiyah Higher Education Assembly under the Presidential Regulation No 87/2017 on Strengthening Character Education (KDP), a test of data credibility, data analysis method through reflective thinking and content analysis. Research results: First, religious attitude of AIK educational practice contains theo-anthropocentrism perspectives. Second, the emergence of moderate attitudes is specifically indicated by being critical and open in accepting differences. Third, smart attitudes contribute to the formation of educated people with good character who are expected to have integrity and ethical awareness.